PENGARUH AUDIT DELAY, OPINI AUDIT, DAN FINANCIAL DISTRESS TERHADAP AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS SUBSEKTOR FOOD & BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022) - Sujiati, Alya Ifayani; Mukti, Aloysius Harry; Sianipar, Panata Bangar Hasioan (SENTRI: Jurnal Riset Ilmiah, 2024)
This study aims to examine the Effect of Audit Delay, Audit Opinion, and Financial Distress on Auditor Switching. The population in this study is sector Consumer Non Cyclicals subsector Food & Beverage companies listed on the Indonesia Stock Exchange in 2020-2022. The variables used in this study are Auditor Switching as the dependent variable; and Audit Delay, Audit Opinion, and Financial Distress Set as an independent variable. The sampling technique used is the purposive sampling method and obtained as many as 201 years of the company. The results showed that the Audit Delay had a positive effect on Auditor Switching, Audit Opinion had no effect on Auditor Switching, and Financial Distress had a positive effect on Auditor Switching.